1976
DOI: 10.3181/00379727-151-39289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin B12 and Folate on Biosynthesis of Methionine from Homocysteine in the Nematode Caenorhabditis briggsae

Abstract: The roles of dietary vitamin B12 and folic acid in methionine biosynthesis from homocysteine were first observed in higher animals. Jukes, Stokstad, and Broquist (1) noted that the growth of vitamin BIZ-deficient chicks was increased by either methionine or homocysteine and vitamin B,, but not by homocysteine alone. It was also reported that rats were able to utilize homocysteine in lieu of methionine when folic acid (2) or choline (3) was added to the diet. In microorganisms, Escherichia coli is known to poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…1C). Cytochrome c or hemoglobin also sustained worm growth, supporting previous studies that have shown heme and vitamin B12, another tetrapyrrole, as necessary factors for C. briggsae development (8,9,34). Our observations that worms can develop to the L4 stage in the absence of exogenous heme in the growth medium suggest that either there are trace amounts of heme in the medium or, more plausibly, maternal heme stored in the egg during embryogenesis is able to sustain early larval growth.…”
Section: Resultssupporting
confidence: 75%
“…1C). Cytochrome c or hemoglobin also sustained worm growth, supporting previous studies that have shown heme and vitamin B12, another tetrapyrrole, as necessary factors for C. briggsae development (8,9,34). Our observations that worms can develop to the L4 stage in the absence of exogenous heme in the growth medium suggest that either there are trace amounts of heme in the medium or, more plausibly, maternal heme stored in the egg during embryogenesis is able to sustain early larval growth.…”
Section: Resultssupporting
confidence: 75%
“…From these results we conclude that no methyltransferase enzyme occurs in spargana of S. mansonoides. The absence of methyltransferase activity in both A. suum and the cat ascarid provides an interesting contrast with the findings of Lu et al (1976). These investigators have presented presumptive evidence for the presence of the methyltransferase enzyme in the free-living nematode, Caenorhabditis briggsae.…”
Section: Resultsmentioning
confidence: 61%
“…The metabolism and intracellular recycling of methionine requires vitamin B12 as cofactor and methyltetrahydrofolate as co-reactant [27,28,29]. In fact, both vitamin B12 and folic acid are required for the biosynthesis of methionine from homocysteine [30]. The beneficial effects of folate in the above conditions can be explained largely within the context of folate-dependent pathways, such as methionine, purine and pyrimidine biosynthesis [31].…”
Section: Intracellular Recycling Of Methioninementioning
confidence: 99%